Lung Acetate Levels Decline in Correlation With Increased Type 2 Allergic Markers in a House Dust Mite Allergic Mouse Model - Roos E. M. Verstegen; Rolf W. Sparidans; Atanaska I. Kostadinova; Johan Garssen; Gert Folkerts; Rudi W. Hendriks; Linette E. M. Willemsen (Clinical and Translational Allergy)
ABSTRACT Aims Microbial dysbiosis is an important feature in allergic asthma. Short‐chain fatty acids (SCFA) produced by the intestinal microbiome play a role in the gut‐lung axis. Little is known about how the gut SCFA levels reflect SCFA levels in other tissues and how these link to the allergic asthma inflammatory status. Materials and Methods Male BALB/c mice were intranasally exposed to house dust mite (HDM) to induce allergic airway inflammation. Acetate, propionate, and butyrate levels were determined in caecum content, serum and lungs of control and HDM‐allergic mice using liquid chromatography‐mass spectrometry. Faecal microbiome composition was determined by DNA sequencing. Results Mean acetate:propionate:butyrate ratios were 75:15:10 in caecum content, 98:1.5:0.5 in serum, and 38:61:1 in the lung. SCFA levels did not correlate across compartments and propionate was relatively high in the lungs. The faecal microbiome of allergic mice differed from control, with increased Desulfovibrionaceae abundance. The lung acetate proportion was lower in allergic mice compared to control. In allergic mice, declining lung acetate levels correlated with increased HDM‐specific IgE in serum and IL‐13 release by ex vivo HDM‐restimulated lung cells. Ex vivo acetate supplementation did not inhibit HDM‐restimulated lung cell IL‐13 production, while butyrate and propionate did. Conclusions Overall, HDM‐driven murine allergic airway inflammation induced changes in the faecal microbiome and reduced acetate in serum and lung tissue. Hereby, lung acetate levels correlated negatively with sensitisation and type‐2 inflammation, but acetate itself did not suppress ex vivo HDM‐induced cytokine release. Our findings provide new insights on the systemic effects of HDM‐allergic inflammation along the gut‐lung axis.